Silken prey - Sandford, John, 1944- (G. P. Putnam's Sons, 2016)
Murder, scandal, political espionage, and an extremely dangerous woman . . . The extraordinary new Lucas Davenport thriller from the #1 New York Times - bestselling author and Pulitzer Prize winner. At 1:15 a.m., a Minnesota political fixer answers his doorbell. The next thing he knows, he's waking up on the floor of a moving car, lying on a plastic sheet, his body wet with blood. When the car stops, a voice says, "Hey, I think he's breathing," and another voice says, "Yeah? Give me the bat." And that's the last thing he ever knows. Lucas Davenport is investigating another case when the trail leads to the man's disappearance, then - very troublingly - to the Minneapolis police department itself, and then - most troublingly of all - to a woman who could give Machiavelli lessons. She has very definite ideas about the way the world should work, and the money, ruthlessness, and sheer will to make it happen. No matter who gets in the way.